A Systematic Review of the Influence of Online Review Content on Travelers' Safety Perceptions - Iswanto, Dedy; Irsyad, Ziqrurrahman; Febrina Lina, Lia; Angelica Cindiyasari, Shiwi; Muhammad Waqas, Hafiz; Fuzail, Muhammad (Jurnal Manajemen dan Inovasi (MANOVA), 2026)
Abstract Introduction : Post-crisis, tourism destinations must rebuild visitor confidence and manage their image. eWOM (electronic word of mouth) and online reviews are critical tools in shaping safety perceptions and maintaining tourist visits. Objective : This study reviews the influence of eWOM on travelers' safety perceptions and revisit intentions after crises, exploring how digital platforms mediate these effects and the role of cultural background in interpreting eWOM related to safety. Methodology : A systematic literature review was conducted using the PRISMA framework, based on Scopus articles published from 2020 to 2025, complemented by bibliometric analysis using VOSviewer. Results : eWOM and UGC on social media significantly impact safety perceptions and revisit intentions. Emotional and visual content in reviews shapes how tourists interpret safety, with cultural factors influencing these perceptions. Algorithms on digital platforms create biases in the visibility of eWOM, affecting safety perceptions. Discussion : eWOM is essential in post-crisis recovery, with digital platforms mediating the influence on safety perceptions. The emotional tone and visual aspects of eWOM, along with algorithms, play key roles in shaping how tourists assess safety and loyalty. Originality/Value : This study provides insights into how eWOM influences tourists' safety perceptions and loyalty post-crisis, offering practical guidance for destination managers to restore trust and manage their image through eWOM.